Alternative explanations of under-pricing of Chinese initial public offerings - Yuan, Jie (2009)
The thesis contains an empirical study designed to reveal why initial public offerings (IPO) of common stocks (A-share) in China are on average under-priced from alternative angles as opposed to more established theories, using a dataset of 880 IPOs from January 1996 to December 2003.